Fascin expression in colorectal carcinomas - Ozerhan, Ismail Hakki (2010)
PURPOSE: The purpose of this study was to investigate the significance of fascin expression in colorectal carcinoma. METHODS: This is a retrospective study of 167 consecutive, well-documented cases of primary colorectal adenocarcinoma for which archival material of surgical specimens from primary tumor resections were available. We chose a representative tissue sample block and examined fascin expression by immunohistochemistry using a primary antibody against "fascin". We calculated the "immunohistochemical score (IHS)" of fascin for each case, which was calculated from the multiplication of scores for the percentage of stained cells and the staining intensity. RESULTS: Fascin immunoreactivity was observed in 59 (35.3%) of all cases with strong reactivity in 24 (14.4%), moderate reactivity in 25 (14.9%) and weak reactivity in 10 (6.0%) cases. Strong/moderate immunoreactivities were mostly observed in invasive fronts of the tumors or in both invasive and other areas. Fascin immunoreactivity scores were significantly higher in tumors with lymph node metastasis (p:0.002) and advanced stage presentation (p:0.007). There was no relation between fascin expression and age, gender, depth of invasion, distant metastasis or histological grade (p>;0.05). There was a higher and statistically significant correlation between fascin immunoreactivity in the invasive borders of tumors and lymph node metastasis (r:0.747, p:0.005). In stage III/IV tumors, two-year survival was 92.2% in tumors without fascin immunoreactivity, and only 60.0% in tumors with a fascin IHS>;10 (p:0.003). CONCLUSION: These findings suggest that fascin is heterogeneously expressed in approximately one third of colorectal carcinomas with a significant association with lymph node metastasis, tumor stage and location. Moreover, these results indicate that fascin may have a role in the lymph node metastasis of colorectal carcinomas